Model Kodifikasi Knowledge pada Perpustakaan Universitas Kristen Satya Wacana dalam Menyediakan Bahan Pustaka - Kevin Mikhail Tulenan; Eko Sediyono (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
Satya Wacana Christian University Library will be running smoothly when the knowledge contained in libraries is well documented. Documentation of the library will be material to members of the library that will come from members of their existing library. The presence of this documentation can solve the problems in the library associated with the provision of library materials. In solving the problem of documentation need a strategy and that strategy is a knowledge management strategy. The method used is based upon the knowledge management strategy is a process of gathering knowledge in the library and provide code on codification of knowledge can be called knowledge. So that the codification knowledge can be accessed and reused easily. Results of this study resulted in the codification knowledge in libraries Satya Wacana Christian University in Provides Library Materials that can be useful to the members involved in the library.